Spanish verb drills - Bey, Vivienne; Concheff, Beatrice Jorgensen; Yates, Jean (New York McGraw-Hill Education, 2017)
A Spanish verb workbook containing lessons, chapter reviews, and conjugation and vocabulary exercises with answers.
"Perfect for beginning & intermediate learners!"--Cover.
Includes index of infinitives, English to Spanish.
Text in English and Spanish.
Keywords: Spanish language -- Verb; Spanish language -- Textbooks for foreign speakers -- English; Spanish language -- Verb -- Problems, exercises, etc